Molecular characterization of bacterial isolates and microbiome: study of mastitic milk, bulk tank milk, and cheese processing plants - Rodrigues, Marjory Xavier (2016)
The present study aimed to evaluate bacterial isolates and the microbiome of dairies. The specific aims were: to characterize Staphylococcus spp. isolated from mastitic milk, to evaluate the presence of Lactococcus in mastitic milk as a potential causative agent of mastitis, to evaluate the association between microbiome and milk quality parameters, and to characterize Staphylococcus spp. isolated from production lines of Minas Frescal cheese. The detection of genes encoding virulence factors (enterotoxins (sea, seb, sec, sed, see, seg, seh, sei, selj, selk, sell, selm, seln, selo, selp, seIq, ser, ses, set, selu, selv, and selx), hemolysins (hla, hlb, hld, hlg, and hlgv), exfoliative toxins (eta, etb, and etd), Panton-Valentine leukocidin (pvl), and toxic shock syndrome toxin (tst)), genes encoding antibiotic resistance (resistance to tetracycline (tetK, tetL, and tetM), erythromycin (ermA, ermB, and ermC), methicillin (mecA and mecC), and tobramycin (ant(4\')-Ia)), molecular typing (spa, SCCmec, and agr types), and phenotyping regarding antibiotic resistance were performed in staphylococci isolates from mastitic milk, and from cheese processing plant samples. Staphylococcus aureus was identified in the majority of isolates from both origins. Several virulence factor genes were detected. The distribution of genes encoding staphylococcal enterotoxins (85.0% - 85.7% of isolates were positive for one or more enterotoxin gene) was highlighted and the gene related to H toxin was the most prevalent. Methicillin-resistant Staphylococcus aureus were identified in isolates from mastitic milk (4.1%) and cheese processing (6.0%); the genotyping and phenotyping of these isolates were described. t605 had the highest frequency in the S. aureus population studied. In mastitic milk, Lactococcus was suggested as the causative agent of an outbreak of mastitis in a dairy farm. Using next generation sequencing, the abundance of Lactococcus was observed in microbiome samples. Bacterial isolation and DNA sequencing confirmed the presence of Lactococcus lactis and Lactococcus garvieae. The microbiome of environmental samples and bulk tank milk from the dairy farm showed the Lactococcus genus among the most common bacterial taxa, suggesting other sources of this genus. Regarding milk quality parameters, the microbiome of bulk tank milk from several dairy farms was associated with somatic cell count and bacterial count. The core microbiome was described and many genera of importance were identified. Among the associations performed between microbiome and milk quality parameters, the identification of Streptococcus in samples classified with high somatic cell count and high bacterial count was highlighted. Several bacterial taxa with relative abundance significantly higher in samples classified as high and low cell count and bacterial count were shown. Real-time polymerase chain reaction was also performed associated with bacterial diversity, bacterial taxa, and bacterial count. These findings highlight the need to control and prevent bacterial contamination in the dairy industry, from herd to consumers.